Quantitative evaluation of dissolution profiles - from simple approaches to advanced chemometrics - Komsta, Łukasz; Wicha-Komsta, Katarzyna (Archives of Pharmacy, 2024)
Many forms of drugs are designed to undergo dissolution upon oral administration. The kinetics and efficiency of this process are critical parameters to be controlled. The methods of its evaluation are described in official guidelines issued by the Food and Drug Administration (FDA), European Medicines Agency (EMA) and World Health Organization (WHO). Many approaches of comparison have been proposed, because these guidelines are not limited to a particular mathematical method. This review summarizes the current state of this topic, covering both model-dependent and model-independent methods, as well as multivariate ideas. The references have been chosen to be the most important papers in the field, so that they can be treated by the reader as the best possible recommendations for further reading.